The Mediating Role of Customer Satisfaction in the Effect of Perceived Enjoyment on Customer Trust in Online Investment Application - Rifki Hanif; Widji Astuti; Sunardi Sunardi (Trescode Green Organization, 2024)
This study aims to analyze the influence of perceived enjoyment on trust in online mutual fund investors through customer satisfaction with the Bibit mutual fund application. Data were collected through questionnaires distributed to users of the Bibit Mutual Fund application. The research population consisted of all Bibit application users in the area of Malang City, East Java – Indonesia, and a sample of 120 users was selected using purposive sampling. The research instrument employed a questionnaire with 24 statements. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal a significant influence of perceived enjoyment on customer trust mediated by customer satisfaction with the Bibit mutual fund application. In conclusion, customer satisfaction serves as a mediating variable between perceived enjoyment and user trust in the Bibit Mutual Fund application. This research contributes to understanding the dynamics of user experience and satisfaction in the context of online investment platforms, emphasizing the pivotal role of satisfaction in fostering customer trust.